Study of Nano Mechanical and Nano Structure on Titanium Nitride (TIN) Coating Prepared by RF Magnetron Sputtering - Renjith Nimal, R.J. Golden; Aditya, Iyer; Gokulamukundhan; Kumar, Harish; Jerson, J. (International Journal of Psychosocial Rehabilitation, 2019)
Titanium nitride (TiN) coating is one of the foremost used thin films. TiN coating ready on low-carbon steel substrate by DC Magnetron sputtering. Its smart producing sturdiness and low value. The structure and properties can be characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), nanoindentation, and tribological. The small structural features and corrosion performance are going to be compared, as are the layers of coating and enhancing the corrosion performance of periodical vapor deposition PVD TiN-coated steel. The result can expect to point the entire rate may well be scaled back by half with relevance steel once this type of coating is employed. The liquid corrosion behavior of the chemical compound coating (TiN) is powerfully passionate about the microdefect density of the coating.